Swamp candles : poems - Burns, Ralph, 1949- (Iowa poetry prize., 1996)
In his convincing and highly accomplished fifth book, Ralph Burns draws on his deep practice and experience. His tones, forms, and subjects are various and striking, the work of a poet mature and courageous enough to range through the full spectrum of his emotions.